Introduction to Epidemiology and Control of Peste des Petits Ruminants (Eco-PPR). 9 Sampling Strategy—Site selection, sample size and Biophysical sample labeling - Wieland, Barbara; Dione, Michel M.; Okoth, Edward A.; Jones, B.; Kotchofa, Pacem; Ilboudo, Guy S.; Campbell, Zoë A.; Rutto, Erick (International Livestock Research Institute, 2020)
This is an overview of the sampling strategy for all studies in the ECo-PPR project.